2021
DOI: 10.1177/00315125211056865
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of a Functional Strength Training Intervention on Movement Quality and Physical Fitness in Adolescents

Abstract: This study compared a 12 week Functional Strength Training (FST) program on functional movement and physical performance to typical physical education (PE) classes for middle school (MS) and high school (HS) students. We randomly assigned 266 participants ( M age = 14.35, SD = 0.57 years; M height = 164.82, SD = 6.13 cm; M mass = 55.09, SD = 12.19 kg; M BMI = 20.11, SD = 3.54 kg/m2) into an FST or control group. The FST group trained in flexibility and stability, functional movement patterns, and health-relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…In total, 20 studies were selected in this study, including 15 RCTs [ 8 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ] and 5 non-RCTs [ 45 , 46 , 47 , 48 , 49 ]. All were published between 2016 and 2022 as peer-reviewed articles or dissertations.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In total, 20 studies were selected in this study, including 15 RCTs [ 8 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ] and 5 non-RCTs [ 45 , 46 , 47 , 48 , 49 ]. All were published between 2016 and 2022 as peer-reviewed articles or dissertations.…”
Section: Resultsmentioning
confidence: 99%
“…The score of 15 RCTs was between 6 and 8 points, with an average score of 6.33 points, indicating the quality of RCTs was good. Two studies were randomly assigned with concealed allocation [ 36 , 44 ]; three studies were blinded, one of which was a double-blind trial [ 32 ], and two were a single-blind trial [ 36 , 42 ]. The scores of the five non-RCT studies were between 15 and 18 points, with an average score of 16 points, indicating that the non-RCTs were medium quality.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…According to the characteristics of different sports, athletes of each sport and even each individual should have different recovery methods. Only by finding the best recovery method can the best recovery effect be achieved [1][2] . In the research on the intervention effect of cold bath on the recovery effect of resistance training , many scholars have studied it and achieved good results, for example : Moghadam BH et al found that compared with the control group (-16.5%), TWI (30min in water at 29°C) helps maintain peak leg muscle power (-4.1%) after 24h downhill running [3].…”
Section: Introductionmentioning
confidence: 99%